PERFORMING TRANSCATHETER AORTIC VALVE IMPLANTATION IN PATIENTS WITH CAROTID STENOSIS - Veselin Valkov; Dobrin Kalchev; Atanas Kostadinov; Branimir Kanazirev (Peytchinski Publishing, 2016)
The management of carotid artery disease in patients with severe aortic stenosis referred for transcatheter aortic valve implantation is challenging. By reviewing the very limited amount of literature we will try to answer the question should we perform carotid revascularization before or after the TAVI procedure.